Comparative Assessment Model of Energy Security and The Level of Industry and Service Development in The European Context - Mihaela Adina MATEESCU; Mihai SabinMUSCALU; Elena Manuela ISTOC; Daniela Nicoleta BALEANU (Communications of International Proceedings, 2024)
This paper presents an analysis of the level of industry and service development regarding energy security both for Romania and for the countries of the European Union during 2020-2022. Thus, to carry out this study, two composite indicators were used, namely: a composite indicator represents the level of energy security taking into account the price of energy, the structure of the energy mix, and the economic, social, political, and environmental objectives and a composite indicator represents the level of industry and service development.
Keywords: energy security; development of industry and services; analysis model